2020
DOI: 10.1155/2020/9132720
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Cognitive Improvement Is Associated with Sodium Channel-Mediated Excitability in APP/PS1 Mice

Abstract: Elevated brain activation, or hyperexcitability, induces cognitive impairment and confers an increased risk of Alzheimer's disease (AD). Blocking the overexcitation of the neural network may be a promising new strategy to prevent, halt, and even reverse this condition. Physical exercise has been shown to be an effective cognitive enhancer that reduces the risk of AD in elderly individuals, but the underlying mechanisms are far from being fully understood. We explored whether long-term treadmill exercise attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…The abnormal expression and distribution of Nav1.6 was reported to be associated with various neurological disorders that characterized by neuronal hyperexcitability [21]. Moreover, we found that exercise training improved cognitive de cient of APP/PS1 mice mainly by altering the expression and distribution of Nav1.1α, Nav1.2 and Nav1.6 [22]. Therefore, to maintain the normal expressions and functions of Nav1.1α, Nav1.2 and Nav1.6 may be the key target for various treatments induced-improvement in cognitive and memory of AD.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The abnormal expression and distribution of Nav1.6 was reported to be associated with various neurological disorders that characterized by neuronal hyperexcitability [21]. Moreover, we found that exercise training improved cognitive de cient of APP/PS1 mice mainly by altering the expression and distribution of Nav1.1α, Nav1.2 and Nav1.6 [22]. Therefore, to maintain the normal expressions and functions of Nav1.1α, Nav1.2 and Nav1.6 may be the key target for various treatments induced-improvement in cognitive and memory of AD.…”
Section: Introductionmentioning
confidence: 62%
“…Meanwhile, PNS is a medicine made of two or more ingredients, of which ginsenoside Rb1(Rb1) is a major component [6]. Rb1 has been shown to enhance the neuroprotective effect of neurons by upregulating brain-derived neurotrophic factor (BDNF) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Even the treatment of exogenous soluble Aβ 1-42 , which is the main secreted marker in the brain of AD patients, could also increase the Na v1.6 channel expression level. Previous studies showed increased excitability in mature cultured APP/PS1 neurons with the increased expression levels of sodium channels, especially the AISlocalized Na v1.6 channel [52,54,62,63]. These neurons were reported with a higher AP ring frequency and a lower threshold upon injecting a strong depolarizing current (i.e., 200 pA, 500 ms).…”
Section: Discussionmentioning
confidence: 89%
“…Axonal pathology in APP/PS1 neurons, accompanied by membrane proteins and ion channel alterations, could seriously affect intrinsic neuronal excitability [52][53][54][55]. In the present study, we found that wild-type neuron and APP/PS1 neurons have normal resting potential (WT: -69.1 ± 0.98 mV, n = 77; APP/PS1: -67.1 ± 0.82 mV, n = 48, ns P value = 0.1703) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Nav β 2-kd induces restoration of sodium current density and neuronal activity in hippocampal neurons, cognitive improvement in APP/PS1 transgenic mice, and promotion of the transformation of APP amyloid metabolic pathway to nonamyloid production process [ 26 ]. Studies have also revealed that cognitive protection induced by either exercise training or notoginsenoside R1 is associated with the regulation of Nav β 2 in the hippocampus of APP/PS1 mice [ 27 , 28 ]. Therefore, the evidence has proved that Nav β 2 plays crucial roles in cognitive dysfunction induced by brain aging and associated disorders, such as AD.…”
Section: Introductionmentioning
confidence: 99%